Clinical characteristics and MRI-based phenotypes of perianal abscess formation in children with fistulizing Crohn's Disease - Tabari, Azadeh; Kaplan, Jess L.; Huh, Susanna Y.; Moran, Christopher J.; Gee, Michael S. (Frontiers in Pediatrics, 2022)
Purpose The aim of this study was to explore potential correlation of the MR imaging features and clinical characteristics with formation of perianal abscess in children with Crohn's perianal fistulas (CPF). Methods From 2010 to 2020, pediatric patients with CPF diagnosis on their first pelvic MRI were identified retrospectively. All patients were divided into two groups based on the presence or absence of perianal abscess. Baseline clinical and MRI characteristics were recorded for each patient. All the statistical calculations were performed using R (version 3.6.3). Results A total of 60 patients [F:M 17:43, median age 14 years (IQR 10-15), ranging 3–18 years] were included in this study. Forty-four abscesses were identified in 36/60 children (mean volume 3 ± 8.6 ml, median 0.3 ml). In 24/60 patients with perianal disease, no abscess was detected on the MRI. Ten patients (28%) showed perianal abscess on pelvic MRI at the initial diagnosis. The rate of active disease on colonoscopy (visible ulcerations/aphthous ulcers) was similar in both groups (95% vs. 94%). With regards to disease location, the majority of patients (40/60, 66.6%) in both groups had ileocolonic CD. All patients without abscess had a single perianal fistula (n = 24; 3 simple and 21 complex fistulae), however, patients with perianal abscess tended to have >1 fistulous tracts (n = 50 fistulas; all complex, 27 single, 10 double and 1 triple). Intersphincteric fistula was the most common fistula type in both groups (79% and 66%, p = 0.1). The total length of fistula (3.8 ± 1.7 vs. 2.8 ± 0.8 cm, p = 0.006) and presence of multiple external openings (n = 25 vs. 7, p = 0.019) were significantly higher in patients with abscesses, and fistula length >3.3 cm showed 80% specificity and 83% PPV for the presence of perianal abscess. Fistulas were symptomatic (pain, bleeding or drainage) at similar rates in both groups (68% and 70%, p = 0.1). Conclusion Pediatric patients with CPF who develop perianal abscess have a distinct imaging phenotype defined by longer fistula length (>3.3 cm), multiple skin openings and multiple fistulous tracts (≥2) on MRI. Patients who have these features but does not have an abscess on imaging may merit more aggressive treatment (and close monitoring) to prevent the development of an abscess.